The assembly and comparative analysis of the first complete mitogenome of Lindera aggregata - Shi, Yujie; Chen, Zhen; Jiang, Jingyong; Wu, Wenwu; Yu, Weifu; Zhang, Shumeng; Zeng, Wei (Frontiers in Plant Science, 2024)
Lindera aggregata, a member belongs to the genus Lindera of Lauraceae family. Its roots and leaves have been used as traditional Chinese medicine or functional food for thousands of years. However, its mitochondrial genome has not been explored. Our aim is to sequence and assemble the mitogenome of L. aggregata to elucidate the genetic mechanism and evolutionary pathway. The results had shown that the mitogenome was extremely complex and had a unique multi-branched conformation with total size of 912,473 bp. Comprehensive analysis of protein coding genes of 7 related species showed that there were 40 common genes in their mitogenome.Interestingly, positive selection had become an important factor in the evolution of ccmB, ccmFC, rps10, rps11 and rps7 genes. Furthermore, our data highlighted the repeated trend of homologous fragment migrations between chloroplast and mitochondrial organelles, and 38 homologous fragments were identified. Phylogenetic analysis identified a tree that was basically consistent with the phylogeny of Laurales species described in the APG IV system. To sum up, this study will be helpful to the study of population genetics and evolution of Lindera species.